Peran Remaja Masjid dalam Meningkatkan Partisipasi Keagamaan Peserta Didik di SMP Negeri 19 Surabaya - Dwi Wulandari; Muhammad Fahmi; Fathur Rohman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to analyze the role of Teen Mosque (Remas) in increasing students' religious participation in SMP Negeri 19 Surabaya. Through structured daily, weekly, and annual religious programs, mosque teenagers play an important role in instilling religious values to students. Programs such as morning tadarus, duha prayer, dhuhur prayer, as well as weekly rohis and PHBI activities become a forum for spiritual development for students. In addition, collaboration between Remas, teachers, student council, and external institutions also supports the effective implementation of activities. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews with religion teachers, youth mosque coaches, students, and participatory observation of religious activities at school. The analysis was conducted by describing and interpreting the role of Remas in encouraging students' participation in religious activities. The results showed that the role of mosque teenagers is very significant in increasing students' religious participation, making SMP Negeri 19 Surabaya a school with a strong spiritual atmosphere. Although there are challenges such as the lack of religious awareness among students. The existence of mosque teenagers helps create a religious school environment, so that SMP Negeri 19 Surabaya can be an example in fostering students' spirituality in the environment.